Graphite phase carbon nitride and graphene composite electrothermal film and preparation method thereof

By causing heterogeneous composite structure to cause the composite structure of graphene and graphite nitride, and the high -energy microwave method is used for water heat treatment, the problem of incomplete thermal fever of the graphene electrical film and the inadequate heat fever is not obvious. Performance and simple and safe preparation process.

CN119370834AActive Publication Date: 2025-01-28SOUTHEAST UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311597316.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2025-01-28
Estimated Expiration
2043-11-28

AI Technical Summary

Technical Problem

The existing graphene electric heating film has uneven heating, and the far-infrared heating is not obvious. The traditional preparation method has problems such as low yield, uncontrollable, long preparation cycle, defects and dangers.

Method used

By causing the heterogeneous composite structure by the graphene and graphite nitrogen nitride structure, and the high -energy microwave method is used for water heat treatment, the carbon nitride and the graphene composite thermal film are prepared. This method improves the decentralization and composite uniformity of the material through the interaction and ultrasound processing of the layer.

Benefits of technology

The heating uniformity of graphene electric heating membranes and the improvement of far -infrared thermal performance were achieved, and the preparation process was simplified, and operational safety and preparation efficiency were improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370834A_ABST
    Figure CN119370834A_ABST
Patent Text Reader

Abstract

The invention relates to the field of functional nano material preparation, in particular to a graphite phase carbon nitride and graphene composite electrothermal film and a preparation method thereof. The preparation method comprises the following steps: firstly, heating a nitrogen-rich organic matter by utilizing high-energy microwaves to prepare a graphite-phase carbon nitride (g-C3N4) nanosheet; the g-C3N4 nanosheet is further subjected to a hydrothermal reaction, and a soluble g-C3N4 nanosheet is obtained; then dispersing soluble g-C3N4 nanosheets in a graphene oxide (GO) solution, carrying out ultrasonic dispersion, and carrying out suction filtration on a suspension to obtain a g-C3N4 / GO composite membrane; and finally, carrying out microwave irradiation heating reduction to obtain the graphite phase carbon nitride and graphene (g-C3N4 / rGO) composite electrothermal film. The g-C3N4 nanosheets with good dispersibility and water solubility are added, so that the thermal conductivity of the graphene electrothermal film is superior to that of a pure graphene electrothermal film in the prior art, and the graphene electrothermal film can be used for thermal insulation products; the high-energy microwave irradiation heating rate is higher, the treatment time is shorter, and the method has the advantages of being simple in process, convenient to operate, low in equipment requirement, low in cost, high in treatment efficiency, free of secondary pollution and the like, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The patent of this invention relates to a graphite phase carbon nitride and graphene composite electric heating film and a preparation method thereof, and belongs to the field of functional nanomaterial preparation. Background Art

[0002] Heating, hot water heating, heating system heating and other heating methods are essential industries in the lives of Chinese people. Since this type of heating generally uses coal burning as a heating source, it will also produce polluting gases during heating. With the improvement of people's living standards in my country, people's environmental awareness is getting higher and higher, and zero-emission and zero-pollution green energy is becoming more and more popular. Therefore, electric heating has gradually become the mainstream of heating, and electric heating materials are increasingly used in electric heating therapy, electric heating and other fields.

[0003] As a new type of two-dimensional nanomaterial, graphene is the only two-dimensional free-state atomic crystal discovered so far. Graphene is composed of a single layer of carbon atoms connected by sp 2 The two-dimensional honeycomb crystal structure formed by the close packing of hybrids has extremely high thermal conductivity, excellent electrical properties and mechanical properties, and is regarded as one of the most ideal new thermal conductive materials. Graphene is known to be used in the field of electric heating, see patent CN 109152114 A (September 26, 2023) and patent US2014182063 A1 (July 3, 2014). However, the graphene electric heating film obtained by the above patents has problems such as uneven heating and unclear far-infrared heating, and the thermal properties of graphene cannot be fully utilized.

[0004] In addition, the current methods for preparing graphene mainly include micromechanical exfoliation, chemical exfoliation, vapor deposition, etc. Micromechanical exfoliation is the simplest and most direct method for preparing graphene. It mainly uses the adhesive force of tape to peel off flake graphite and other materials layer by layer through multiple pastings, and then pastes the tape with graphite flakes onto a target substrate such as a silicon wafer. Finally, the tape is removed with solvents such as acetone to obtain graphene with a size of more than 100 μm. This method has a simple operation process, but the yield of this method is low and uncontrollable, which is difficult to meet the large-scale and large-scale preparation of graphene. The chemical exfoliation method uses redox reactions to introduce functional groups on the carbon atoms of the graphite layer, so that the interlayer spacing of the graphite is increased, thereby weakening its interlayer interaction, and then the oxidized graphite layers are separated layer by layer through ultrasound or rapid expansion to obtain oxidized graphene, and finally the oxygen-containing functional groups are removed by chemical reduction or high-temperature reduction to obtain graphene. This method is currently an effective method for preparing graphene in large quantities, but the preparation cycle is long, and the oxidation, ultrasound and subsequent reduction processes often cause the loss of carbon atoms. The prepared graphene contains many defects, resulting in poor conductivity. The chemical vapor deposition method uses carbon-containing compounds such as methane as a carbon source and grows graphene through high-temperature decomposition on the surface of the body. Although the graphene prepared by this method is of high quality and can be grown over a large area, the reactant methane required for the reaction is expensive and the experimental operation process is highly dangerous.

[0005] Therefore, there is an urgent need for a preparation method with the advantages of fast heating speed and easy process control, as well as a composite electric heating film that generates heat evenly and can give full play to the thermal properties of graphene. Summary of the invention

[0006] Heterostructures in which two or more layers of two-dimensional crystals are vertically stacked through interlayer van der Waals interactions have shown extraordinary performance beyond that of individual components and have attracted the attention of more and more researchers in recent years. Since graphene and graphitic carbon nitride have complementary physical properties, they can be constructed into heterocomposite structures to fully exploit the characteristics of each individual component to achieve optimal performance. For example, assembling graphene with graphitic carbon nitride can open the intrinsic band gap of graphene, thereby overcoming the zero band gap barrier of graphene when constructing field effect transistors. Compared with graphitic carbon nitride, hybrid graphene / graphitic carbon nitride heterostructures show enhanced light absorption in the visible light region, which is a promising feature for new photovoltaic and electrothermal applications.

[0007] In view of the shortcomings of the prior art, the present invention provides a method for preparing a graphite phase carbon nitride and graphene composite electric heating film. The prepared material generates heat evenly, and compared with traditional heating methods, the preparation method has simple experimental operation, safe and effective process, and strong repeatability.

[0008] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a graphite phase carbon nitride and graphene composite electric heating film and a preparation method thereof, including a composite electric heating film.

[0009] The composite electric heating film comprises the following components by weight: soluble gC 3 N 4 Nanosheets, graphene.

[0010] The soluble gC 3 N 4 The mass ratio of nanosheets to graphene is 0.1 to 5:1.

[0011] (1) The nitrogen-rich organic matter is added into a quartz crucible, and then the crucible is placed into a high-energy microwave oven resonant cavity for irradiation treatment to obtain a light yellow gC 3 N 4 powder;

[0012] (2) The powder is uniformly dispersed in deionized water, and the mixture is subjected to ultrasonic treatment for 0.5 to 2 hours; after the hydrothermal treatment, the mixture is cooled to room temperature, washed with deionized water and freeze-dried overnight to obtain soluble gC 3 N 4 Nanosheets;

[0013] (3) First, GO was prepared by the Hummers method: graphite, sodium nitrate, and potassium permanganate were weighed in an ice bath in a ratio of 1:1:3, and then concentrated sulfuric acid was slowly added dropwise into a three-necked flask containing graphite and stirred. 3 ) and mix well, then weigh potassium permanganate (KMnO 4 ) were added to the three-necked flask in batches, and the mixture was stirred continuously and reacted in a water bath; after adding deionized water to dilute the solution, hydrogen peroxide (H 2 O 2 ) is gradually added into a three-necked flask while stirring until the liquid changes color and separates into layers. The lower layer of golden viscous liquid is filtered and washed with dilute HCl solution and deionized water until it is neutral, thereby obtaining graphene oxide (GO) solution.

[0014] (4) the soluble gC 3 N 4 The nanosheets were dispersed in the GO solution, and then the mixture was put into an ultrasonicator for homogenization. Then, an organic filter membrane with a pore size of 0.22 μm and a vacuum filtration device were used to filter the gC 3 N 4 The mixed dispersion of GO / GO was vacuum filtered, and the composite membrane was placed in a vacuum drying oven and dried at 60 °C for 12 h.

[0015] (5) The composite film is placed in a high-energy microwave oven resonant cavity, the vacuum degree, microwave power, and microwave oven resonant cavity temperature are adjusted, and the reaction is carried out under microwave radiation heating to obtain gC 3 N 4 / rGO composite electric heating film.

[0016] Preferably, the nitrogen-rich organic matter is any one of urea, dicyandiamide, and melamine, or a combination of at least two thereof, such as urea, urea and dicyandiamide, dicyandiamide, dicyandiamide and melamine, melamine, melamine and urea.

[0017] Preferably, the heating power of the high-energy microwave is 3-5 kW, for example, 3 kW, 3.5 kW, 4 kW, 4.5 kW, or 5 kW.

[0018] Preferably, the heating reaction time of the high-energy microwave is preferably 1 to 10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min.

[0019] Preferably, the hydrothermal reaction temperature is preferably 150-200°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C.

[0020] Preferably, the hydrothermal reaction insulation time is preferably 5 to 24 hours, for example, 6 hours, 8 hours, 12 hours, 16 hours, 20 hours, or 24 hours.

[0021] Preferably, the stirring time is preferably 10 to 15 min, for example, 10 min, 11 min, 12 min, 13 min, 14 min, or 15 min.

[0022] Preferably, the reaction time is 2 to 3 h, for example, 2 h, 2.5 h, or 3 h.

[0023] Preferably, the reaction temperature is 35-40°C, for example, 35°C, 36°C, 37°C, 38°C, 39°C, or 40°C.

[0024] Preferably, the reaction time is 3 to 5 h, for example, 3 h, 4 h, or 5 h.

[0025] Preferably, the reaction temperature is preferably 90-98°C, for example, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C.

[0026] Preferably, the ultrasonic time is 1 to 2 hours, for example, 1 hour, 1.5 hours, or 2 hours.

[0027] Preferably, gC3 N 4 In the / rGO composite membrane, soluble gC 3 N 4 The mass ratio to rGO is preferably 0.2-3:1, for example 0.2:1, 0.5:1, 1:1, 1.2:1, 1.5:1, 2:1, 2.2:1, 2.5:1.

[0028] Preferably, the heating power of the high-energy microwave is 3-5 kW, for example, 3 kW, 3.5 kW, 4 kW, 4.5 kW, or 5 kW.

[0029] Preferably, the heating reaction time of the high-energy microwave is preferably 1 to 10 s, for example, 5 s, 6 s, 7 s, 8 s, 9 s, or 10 s.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention provides a method for preparing a graphite phase carbon nitride and graphene composite electric heating film, wherein the surface of carbon nitride nanosheets is modified by a simple hydrothermal method, so that the dispersibility of carbon nitride in aqueous solution is improved, and the uniform composite of carbon nitride and graphene is further enhanced.

[0032] 2. Carbon nitride has good thermal stability and strong resistance to temperature decay, which can effectively inhibit thermal drift and maintain the stability of its structure. In addition, graphene has very high electrical conductivity. The two complement each other. The superior electron mobility of graphene makes up for the low electrical conductivity of carbon nitride. The composite film of graphite phase carbon nitride and graphene improves the electrical heating performance of graphene electric heating film.

[0033] 3. The present invention uses high-energy microwave method and microwave as a heating tool, which has the characteristics of being able to heat the inside and outside of the material simultaneously without heat conduction and without thermal hysteresis. Compared with the traditional muffle furnace heating of 2 to 6 hours, microwave heating can complete heating within 5 to 10 seconds, with the advantages of fast heating rate, selective heating, energy saving and high efficiency, and easy control. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The figure is a schematic diagram of the preparation of the graphite phase carbon nitride and graphene composite electric heating film of the present invention;

[0035] Figure 2 This is a transmission electron microscope image (TEM) of the graphite phase carbon nitride of the present invention;

[0036] Figure 3 Infrared testing (FT-IR) of graphite phase carbon nitride and soluble carbon nitride of the present invention;

[0037] Figure 4This is a transmission electron microscope image (TEM) of the graphite phase carbon nitride and graphene composite electric heating film of the present invention; DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention.

[0039] Reagents used in the examples: melamine, Shanghai McLean Biochemical Technology Co., Ltd.; graphite powder, Shanghai McLean Biochemical Technology Co., Ltd.; sulfuric acid, Shanghai Aladdin Reagent Co., Ltd.; nitric acid, Shanghai Aladdin Reagent Co., Ltd.; hydrochloric acid, Shanghai Aladdin Reagent Co., Ltd.; potassium permanganate, Sinopharm Chemical Reagent Co., Ltd.; hydrogen peroxide, Sinopharm Chemical Reagent Co., Ltd.

[0040] Instruments used in the examples: hydrothermal kettle, Anhui Kemi Mechanical Technology Co., Ltd.; microwave oven (NJZ10-3), Nanjing Jiequan Microwave Equipment Co., Ltd.; centrifuge (TG16-WS), Hunan Xiangyi Laboratory Instrument Development Co., Ltd.; vacuum oven (DZF-605), Shanghai Jinghong Experimental Equipment Co., Ltd.; transmission electron microscope (Tecnai G2), ThermoFisher Scientific (FEI) Company, USA; Fourier transform infrared spectrometer (Nicolet 5700), Thermo Electric Corporation, USA.

[0041] Example 1

[0042] S1: Weigh 10g of melamine and 0.15g of carbon fiber respectively, mix them evenly and add them into a quartz crucible, then place the crucible into the resonant cavity of a high-energy microwave oven. Use a water ring pump to evacuate the resonant cavity to 1×10 4 Pa, and the circulating water cooling device was turned on, and melamine was irradiated at a microwave power of 4 kW for 10 min to obtain graphite phase carbon nitride nanosheets (gC 3 N 4 Nanosheets);

[0043] S2: weigh 1g gC 3 N 4 Dispersed in 50 mL of deionized water, the mixed solution was then transferred to a reactor and kept at 180 °C for 10 h to obtain soluble gC 3 N 4 .

[0044] S3: Graphene oxide (GO) was prepared by Hummers oxidation method. Specifically, 1 g of graphite powder was placed in a three-necked flask, ice-bathed to 0 °C, sulfuric acid and sodium nitrate were added and stirred evenly, the temperature was maintained at 0-4 °C, 3 g of potassium permanganate was added, the temperature was raised to 30-40 °C, stirred until a brown paste was formed, diluted with water, stirred for 0.5 h, and 1 mL of H 2 O 2 , react, filter, wash the product with 20 mL of hydrochloric acid to remove chloride ions, centrifuge, and dry at 60-70°C for 24 h to obtain GO.

[0045] S4: Weigh 20% of the mass of GO gC 3 N 4 Then, the gC 3 N 4 The mixed dispersion of GO / GO was vacuum filtered, and the composite membrane was placed in a vacuum drying oven and dried at 60 °C for 12 h.

[0046] S5: gC 3 N 4 The gC / GO composite film was placed in a microwave resonant cavity and the microwave resonant cavity was evacuated to a vacuum. 3 N 4 The irradiation treatment of the / GO composite film was carried out for 2-10s to obtain graphite phase carbon nitride / redox graphene (gC 3 N 4 / rGO) composite membrane.

[0047] Figure 1 Schematic diagram of the preparation of graphite phase carbon nitride and graphene composite electric heating film.

[0048] The following section briefly explains its material characteristics:

[0049] C 3 N 4 / rGO composite membrane electrothermal performance test: Copper foil is attached to both ends of the electrothermal film as electrodes, a DC regulated power supply is used as a power supply to provide an external voltage, a conductive path is formed by connecting with wires, and a thermocouple sensor and a multi-channel temperature tester are used to record the temperature change of the electrothermal film to characterize the electrothermal performance of the electrothermal film. The voltage is set to 10V, the heating time is 10min, and the tests are performed 3 times respectively to take the average value.

[0050] C 3 N 4 / rGO composite film resistivity test: First, use a digital micrometer (TESA digital micrometer, Switzerland) to measure the thickness of at least 6 points of the electric heating film, and take the average h. Then use a four-probe (FT-341, Ruike Instrument) tester to test the square resistance of these 6 points respectively, and take the average value Rs. The volume resistivity of the electric heating film is Rv = Rs × h.

[0051] C 3 N 4 / rGO composite film flexibility test: First test the resistance Rv of the electric heating film, then bend the electric heating film on a circular axis, and measure its resistance Rt after every 10 bends, ΔR = |Rt-Rv|. The flexibility of the electric heating film is measured according to the value of ΔR / Rv.

[0052] C 3 N 4 / rGO composite film heating uniformity test: Use an infrared thermal imager to measure the changes in temperature and distribution uniformity of the sample during the power-on heating process. When the electric heating film is in a stable working state, the nine-square grid method (i.e., the electric heating film is divided into 9 relatively uniform rectangular areas) is used to divide the area within 30 mm of the heating contour edge of the electric heating film into 9 areas, measure the highest temperature in each area, and take the difference between the maximum and minimum values ​​of the 9 highest values ​​to obtain the temperature non-uniformity of the electric heating film.

[0053] Example 2

[0054] S1: Weigh 10g of dicyandiamide and 0.15g of carbon fiber respectively, mix them evenly and add them into a quartz crucible, then place the crucible into the resonant cavity of a high-energy microwave oven. Use a water ring pump to evacuate the resonant cavity to 1×10 4 Pa, and start the circulating water cooling device, irradiate melamine at 5kW microwave power, keep warm for 5min, and obtain gC 3 N 4 ;

[0055] S2: weigh 1g gC 3 N 4 Dispersed in 50 mL of deionized water, the mixed solution was then transferred to a reactor and kept at 180 °C for 15 h to obtain soluble gC 3 N 4 .

[0056] S3: Graphite oxide GO was prepared by Hummers oxidation method. Specifically, 1 g of graphite powder was placed in a three-necked flask, ice-bathed to 0 °C, sulfuric acid and sodium nitrate were added and stirred evenly, the temperature was maintained at 0-4 °C, 3 g of potassium permanganate was added, the temperature was raised to 30-40 °C, stirred until a brown paste was formed, diluted with water, stirred for 0.5 h, and 1 mL of H 2 O 2, react, filter, wash the product with 20 mL of hydrochloric acid to remove chloride ions, centrifuge, and dry at 60-70°C for 24 h to obtain GO.

[0057] S4: Weigh 20% of the mass of GO gC 3 N 4 Then, the gC 3 N 4 The mixed dispersion of GO / GO was vacuum filtered, and the composite membrane was placed in a vacuum drying oven and dried at 60 °C for 12 h.

[0058] S5: gC 3 N 4 The gC / GO composite film was placed in a microwave resonant cavity and the microwave resonant cavity was evacuated to a vacuum. 3 N 4 The gC / GO composite film was irradiated and kept warm for 2-10s to obtain 3 N 4 / rGO composite membrane.

[0059] Example 3

[0060] S1: Weigh 10g of melamine and 0.15g of carbon fiber respectively, mix them evenly and add them into a quartz crucible, then place the crucible into the resonant cavity of a high-energy microwave oven. Use a water ring pump to evacuate the resonant cavity to 1×10 4 Pa, and start the circulating water cooling device, irradiate melamine at 5kW microwave power, keep warm for 10min, and obtain gC 3 N 4 ;

[0061] S2: weigh 1g gC 3 N 4 Dispersed in 50 mL of deionized water, the mixed solution was then transferred to a reactor and kept at 180 °C for 10 h to obtain soluble gC 3 N 4 .

[0062] S3: Graphite oxide GO was prepared by Hummers oxidation method. Specifically, 1 g of graphite powder was placed in a three-necked flask, ice-bathed to 0 °C, sulfuric acid and sodium nitrate were added and stirred evenly, the temperature was maintained at 0-4 °C, 3 g of potassium permanganate was added, the temperature was raised to 30-40 °C, stirred until a brown paste was formed, diluted with water, stirred for 0.5 h, and 1 mL of H 2 O 2 , react, filter, wash the product with 20 mL of hydrochloric acid to remove chloride ions, centrifuge, and dry at 60-70°C for 24 h to obtain GO.

[0063] S4: Weigh 20% of the mass of GO gC 3 N 4 Then, the gC 3 N 4 The mixed dispersion of GO / GO was vacuum filtered, and the composite membrane was placed in a vacuum drying oven and dried at 60 °C for 12 h.

[0064] S5: gC 3 N 4 The gC / GO composite film was placed in a microwave resonant cavity and the microwave resonant cavity was evacuated to a vacuum. 3 N 4 The gC / GO composite film was irradiated and kept warm for 10 seconds to obtain 3 N 4 / rGO composite membrane.

[0065] Example 4

[0066] S1: Weigh 10g of melamine and 0.15g of carbon fiber respectively, mix them evenly and add them into a quartz crucible, then place the crucible into the resonant cavity of a high-energy microwave oven. Use a water ring pump to evacuate the resonant cavity to 1×10 4 Pa, and start the circulating water cooling device, irradiate melamine at 5kW microwave power, keep warm for 5min, and obtain gC 3 N 4 ;

[0067] S2: weigh 1g gC 3 N 4 Dispersed in 50 mL of deionized water, the mixed solution was then transferred to a reactor and kept at 180 °C for 24 h to obtain soluble gC 3 N 4 .

[0068] S3: Graphite oxide GO was prepared by Hummers oxidation method. Specifically, 1 g of graphite powder was placed in a three-necked flask, ice-bathed to 0 °C, sulfuric acid and sodium nitrate were added and stirred evenly, the temperature was maintained at 0-4 °C, 3 g of potassium permanganate was added, the temperature was raised to 30-40 °C, stirred until a brown paste was formed, diluted with water, stirred for 0.5 h, and 1 mL of H 2 O 2 , react, filter, wash the product with 20 mL of hydrochloric acid to remove chloride ions, centrifuge, and dry at 60-70°C for 24 h to obtain GO.

[0069] S4: Weigh 20% of the mass of GO gC 3 N4 Then, the gC 3 N 4 The mixed dispersion of GO / GO was vacuum filtered, and the composite membrane was placed in a vacuum drying oven and dried at 60 °C for 12 h.

[0070] S5: gC 3 N 4 The gC / GO composite film was placed in a microwave resonant cavity and the microwave resonant cavity was evacuated to a vacuum. 3 N 4 The gC / GO composite film was irradiated and kept warm for 10 seconds to obtain 3 N 4 / rGO composite membrane.

[0071] Figure 2 This is a transmission electron microscope photograph of the graphite phase carbon nitride obtained in step 1, which exhibits typical two-dimensional ultra-thin nanosheet morphology characteristics of a graphene-like structure. Figure 2 It is shown in the figure that although multiple nanosheets are stacked together, they are still relatively transparent, which indicates that the thickness of the obtained product is extremely thin.

[0072] Example 5

[0073] S1: Weigh 10g of melamine and 0.15g of carbon fiber respectively, mix them evenly and add them into a quartz crucible, then place the crucible into the resonant cavity of a high-energy microwave oven. Use a water ring pump to evacuate the resonant cavity to 1×10 4 Pa, and start the circulating water cooling device, irradiate melamine at 5kW microwave power, keep warm for 10min, and obtain gC 3 N 4 ;

[0074] S2: weigh 1g gC 3 N 4 Dispersed in 50 mL of deionized water, the mixed solution was then transferred to a reactor and kept at 180 °C for 24 h to obtain soluble gC 3 N 4 .

[0075] S3: Graphite oxide GO was prepared by Hummers oxidation method. Specifically, 1 g of graphite powder was placed in a three-necked flask, ice-bathed to 0 °C, sulfuric acid and sodium nitrate were added and stirred evenly, the temperature was maintained at 0-4 °C, 3 g of potassium permanganate was added, the temperature was raised to 30-40 °C, stirred until a brown paste was formed, diluted with water, stirred for 0.5 h, and 1 mL of H 2 O 2, react, filter, wash the product with 20 mL of hydrochloric acid to remove chloride ions, centrifuge, and dry at 60-70°C for 24 h to obtain GO.

[0076] S4: Weigh 50% of the mass of GO gC 3 N 4 Then, the gC 3 N 4 The mixed dispersion of GO / GO was vacuum filtered, and the composite membrane was placed in a vacuum drying oven and dried at 60 °C for 12 h.

[0077] S5: gC 3 N 4 The gC / GO composite film was placed in a microwave resonant cavity and the microwave resonant cavity was evacuated to a vacuum. 3 N 4 The gC / GO composite film was irradiated and kept warm for 5s to obtain 3 N 4 / rGO composite membrane.

[0078] Example 6

[0079] S1: Weigh 10g of melamine and 0.15g of carbon fiber respectively, mix them evenly and add them into a quartz crucible, then place the crucible into the resonant cavity of a high-energy microwave oven. Use a water ring pump to evacuate the resonant cavity to 1×10 4 Pa, and start the circulating water cooling device, irradiate melamine at 3kW microwave power, keep warm for 10min, and obtain gC 3 N 4 ;

[0080] S2: weigh 1g gC 3 N 4 Dispersed in 50 mL of deionized water, the mixed solution was then transferred to a reactor and kept at 180 °C for 18 h to obtain soluble gC 3 N 4 .

[0081] S3: Graphite oxide GO was prepared by Hummers oxidation method. Specifically, 1 g of graphite powder was placed in a three-necked flask, ice-bathed to 0 °C, sulfuric acid and sodium nitrate were added and stirred evenly, the temperature was maintained at 0-4 °C, 3 g of potassium permanganate was added, the temperature was raised to 30-40 °C, stirred until a brown paste was formed, diluted with water, stirred for 0.5 h, and 1 mL of H 2 O 2 , react, filter, wash the product with 20 mL of hydrochloric acid to remove chloride ions, centrifuge, and dry at 60-70°C for 24 h to obtain GO.

[0082] S4: Weigh 30% of the mass of GO gC 3 N 4 Then, the gC 3 N 4 The mixed dispersion of GO / GO was vacuum filtered, and the composite membrane was placed in a vacuum drying oven and dried at 60 °C for 12 h.

[0083] S5: gC 3 N 4 The gC / GO composite film was placed in a microwave resonant cavity and the microwave resonant cavity was evacuated to a vacuum. 3 N 4 The gC / GO composite film was irradiated and kept warm for 10 seconds to obtain 3 N 4 / rGO composite membrane.

[0084] Example 7

[0085] S1: Weigh 10g of melamine and 0.15g of carbon fiber respectively, mix them evenly and add them into a quartz crucible, then place the crucible into the resonant cavity of a high-energy microwave oven. Use a water ring pump to evacuate the resonant cavity to 1×10 4 Pa, and the circulating water cooling device was turned on, and melamine was irradiated at a microwave power of 4 kW for 10 minutes to obtain gC 3 N 4 ;

[0086] S2: weigh 1g gC 3 N 4 Dispersed in 50 mL of deionized water, the mixed solution was then transferred to a reactor and kept at 180 °C for 24 h to obtain soluble gC 3 N 4 .

[0087] S3: Graphite oxide GO was prepared by Hummers oxidation method. Specifically, 1 g of graphite powder was placed in a three-necked flask, ice-bathed to 0 °C, sulfuric acid and sodium nitrate were added and stirred evenly, the temperature was maintained at 0-4 °C, 3 g of potassium permanganate was added, the temperature was raised to 30-40 °C, stirred until a brown paste was formed, diluted with water, stirred for 0.5 h, and 1 mL of H 2 O 2 , react, filter, wash the product with 20 mL of hydrochloric acid to remove chloride ions, centrifuge, and dry at 60-70°C for 24 h to obtain GO.

[0088] S4: Weigh 20% of the mass of GO gC 3 N 4Then, the gC 3 N 4 The mixed dispersion of GO / GO was vacuum filtered, and the composite membrane was placed in a vacuum drying oven and dried at 60 °C for 12 h.

[0089] S5: gC 3 N 4 The gC / GO composite film was placed in a microwave resonant cavity and the microwave resonant cavity was evacuated to a vacuum. 3 N 4 The gC / GO composite film was irradiated and kept warm for 5s to obtain 3 N 4 / rGO composite membrane.

[0090] Figure 3 This is the infrared test image of graphite phase carbon nitride and soluble graphite phase carbon nitride. It can be seen from the figure that compared with graphite phase carbon nitride, the soluble carbon nitride has many hydrophilic groups (-NH 2 , -OH and -C=O), which makes the soluble carbon nitride have excellent dispersibility and solubility.

[0091] Example 8

[0092] S1: Weigh 10g of melamine and 0.15g of carbon fiber respectively, mix them evenly and add them into a quartz crucible, then place the crucible into the resonant cavity of a high-energy microwave oven. Use a water ring pump to evacuate the resonant cavity to 1×10 4 Pa, and the circulating water cooling device was turned on, and melamine was irradiated at a microwave power of 4 kW for 10 minutes to obtain gC 3 N 4 ;

[0093] S2: weigh 1g gC 3 N 4 Dispersed in 50 mL of deionized water, the mixed solution was then transferred to a reactor and kept at 180 °C for 24 h to obtain soluble gC 3 N 4 .

[0094] S3: Graphite oxide GO was prepared by Hummers oxidation method. Specifically, 1 g of graphite powder was placed in a three-necked flask, ice-bathed to 0 °C, sulfuric acid and sodium nitrate were added and stirred evenly, the temperature was maintained at 0-4 °C, 3 g of potassium permanganate was added, the temperature was raised to 30-40 °C, stirred until a brown paste was formed, diluted with water, stirred for 0.5 h, and 1 mL of H 2 O 2, react, filter, wash the product with 20 mL of hydrochloric acid to remove chloride ions, centrifuge, and dry at 60-70°C for 24 h to obtain GO.

[0095] S4: Weigh 5% of GO mass gC 3 N 4 Then, the gC 3 N 4 The mixed dispersion of GO / GO was vacuum filtered, and the composite membrane was placed in a vacuum drying oven and dried at 60 °C for 12 h.

[0096] S5: gC 3 N 4 The gC / GO composite film was placed in a microwave resonant cavity and the microwave resonant cavity was evacuated to a vacuum. 3 N 4 The gC / GO composite film was irradiated and kept warm for 2-10s to obtain 3 N 4 / rGO composite membrane.

[0097] Figure 4 This is a transmission photo of the graphite phase carbon nitride and graphene composite electric heating film. It can be seen from the figure that gC 3 N 4 Nanosheets and graphene are stacked layer by layer to form a two-dimensional layered structure.

[0098] Comparative Example 1 Preparation of graphite phase carbon nitride by conventional thermal polycondensation method

[0099] At present, the use of thermal polycondensation is a common method for preparing graphite-type carbon nitride. For example, Liang Shijing's research group at Fuzhou University first placed melamine in a muffle furnace and calcined it at 500°C for 4 hours, and synthesized a graphite-like carbon nitride precursor by thermal polycondensation; then the graphite-like carbon nitride was dispersed in an ethanol aqueous solution and ultrasonically treated, and then stirred for a period of time and then ultrasonically peeled, and finally centrifuged to obtain graphene-like carbon nitride (Liang Shijing, Lin Qiuyan, Bi Jinhong, Liu Minghua, A molecular-level thick nanosheet and its preparation method and application, Publication No.: CN103254200A). Although this method can obtain graphite-like carbon nitride, the thermal polycondensation reaction, ultrasonic treatment, stirring, centrifugation and other processing processes of this method make the preparation cycle very long and complicated.

[0100] Comparative Example 2 Preparation of graphene-like carbon nitride by microwave method

[0101] In view of the advantages of microwave synthesis in terms of high efficiency and environmental protection, scientific research institutes such as South China Normal University, Nanjing University, and Anhui University have gradually begun to use microwave heating of melamine to synthesize graphite phase carbon nitride. For example, Wang Xin et al. from South China Normal University (Wang Xin, Yang Liqin, Chen Zhihong, Preparation and Application of Graphite Phase Carbon Nitride under Microwave Conditions, Application No.: CN202110045000.3. Application Publication No.: CN112875660A) used urea as a synthetic raw material and copper oxide as a microwave absorber, and heated for 15 to 25 minutes under microwave (100 to 500W) conditions to quickly obtain graphite phase carbon nitride. However, the separate placement of microwave absorbers and raw materials significantly reduced the thermal efficiency, making it difficult to give full play to the advantages of rapid heating of the microwave irradiated bulk phase, which seriously affected the preparation efficiency.

[0102] Comparative Example 3 Preparation of graphene-like carbon nitride by microwave method

[0103] Professor Yuan Yupeng's team at Anhui University (Yuan Yupeng, Zhao Gege, Du Haiwei, Jiang Daochuan, Zhu Chuhong, a carbon nitride material with n-π* transition and its preparation method, application number: CN202210537783.1. Publication number: CN115159477A) used microwave irradiation with a maximum heating frequency of 900 MHz. After heating for 20 minutes, graphite phase carbon nitride was quickly obtained, but the microwave absorber and the raw material were placed separately, making it difficult to take advantage of the rapid heating of the bulk phase by microwave irradiation.

[0104] Comparative Example 4 Preparation of graphene-like carbon nitride nanosheets by microwave method

[0105] In addition, the research group of Academician Zou Zhigang of Nanjing University first synthesized the precursor by irradiating it with 800W microwave power for 25min, and then carried out high-temperature calcination and etching for 25h, and finally obtained ultra-thin carbon nitride nanosheets with a thickness of 3nm (Gao Jun, Micro-Nano Structure gC 3 N 4 Preparation and Performance Research, Master's Thesis of Nanjing University, 2012,) Its stacking thickness is close to 10 layers, reaching the critical standard of two-dimensional ultra-thin nanosheets with graphene-like structure, but this method has cumbersome steps and is time-consuming.

[0106] In addition, Wang Jigang and others from Zhangjiagang Dongda Industrial Technology Research Institute used high-energy microwave irradiation to directly prepare graphite-like carbon nitride (CN201610065411.8, CN201610908265.0, and CN201710331913.5). However, the above invention patents only obtained graphite-like carbon nitride and applied it to functional fields such as photocatalysis or lubrication, and did not achieve compounding with graphene and application in fields such as electric heating.

[0107] Comparative Example 5 Preparation of graphene and carbon nitride composite materials by conventional thermal polycondensation method

[0108] At present, thermal polycondensation is also a common method for preparing graphite carbon nitride composite materials. For example, Professor Zhao Huijun's team at Griffith University in Australia (Li Y, Zhang H, Liu P, et al. Cross-linked gC 3 N 4 / rGO nanocomposites with tunable band structure and enhanced visible light photocatalytic activity[J].Small,2013,9(19):3336-3344.) Graphene oxide (GO) and cyanamide were first uniformly mixed and then heated to about 550°C in a tubular muffle furnace with argon gas. The former was reduced to rGO by heating and the latter was condensed to generate gC 3 N 4 , and finally generate rGO / gC 3 N 4 However, this method requires a 4-hour preheat treatment, which results in low preparation efficiency. In addition, this method cannot synthesize large-sized ultra-thin carbon nitride nanosheets, resulting in the inability to completely composite carbon nitride and graphene. 3 N 4 The composite material is a powder sample and cannot be used in the field of electric heating film heating.

[0109] Comparative Example 6 Preparation of a Composite of Graphene and Graphite Phase Carbon Nitride by Direct Microwave Heating of Melamine and Graphene Oxide

[0110] Professor Gu Yongpan and Wang Jigang's research group at Southeast University used a mixture of melamine and GO as a precursor and synthesized rGO and gC by microwave method. 3 N 4 The ultra-rapid synthesis of rGO / gC 3 N 4 composite via microwave heating with enhanced photocatalytic performance[J].Materials Letters,2018,232:107-109.), but the presence of GO in the preparation process makes gC 3 N 4 The growth process of rGO and gC 3 N 4The size of the composite is reduced; and the distribution of the prepared product is not uniform. After melamine and GO are mixed in the preparation process, due to the intense and complex reaction process, other intermediates such as melem are present in the synthetic product. In addition, the product prepared by this method is a powder sample and cannot be directly applied in the field of electric heating film heating.

[0111] Comparative Example 7 Graphene Heating Film

[0112] S1: Measure the GO solution, then use an organic filter membrane with a pore size of 0.22 μm and a vacuum filtration device to vacuum filter the G dispersion, place the GO membrane in a vacuum drying oven, and continue drying at a temperature of 60°C for 12 hours.

[0113] S2: placing the GO membrane in a microwave resonant cavity, evacuating the microwave resonant cavity, irradiating the GO membrane at a microwave power of 5 kW, and keeping the temperature for 10 seconds to obtain an rGO membrane.

[0114] Comparative Example 8 Graphene Heating Film

[0115] S1: Measure the GO solution, then use an organic filter membrane with a pore size of 0.22 μm and a vacuum filtration device to vacuum filter the G dispersion, place the GO membrane in a vacuum drying oven, and continue drying at a temperature of 60°C for 12 hours.

[0116] S2: placing the GO membrane in a microwave resonant cavity, evacuating the microwave resonant cavity, irradiating the GO membrane at a microwave power of 5 kW, and keeping the temperature for 5 seconds to obtain an rGO membrane.

[0117] Comparative Example 9 Graphene Heating Film

[0118] S1: Measure the GO solution, then use an organic filter membrane with a pore size of 0.22 μm and a vacuum filtration device to vacuum filter the G dispersion, place the GO membrane in a vacuum drying oven, and continue drying at a temperature of 60°C for 12 hours.

[0119] S2: placing the GO membrane in a microwave resonant cavity, evacuating the microwave resonant cavity, irradiating the GO membrane at a microwave power of 4 kW, and keeping the temperature for 10 seconds to obtain an rGO membrane.

[0120] Table 1 Preparation time schedule

[0121]

[0122] Table 2 Comparison of thermal conductivity and resistivity

[0123]

Claims

1. A method for preparing a graphite phase carbon nitride and graphene composite electric heating film, characterized in that: The composite electric heating film is a two-dimensional layered structure formed by stacking soluble g-C3N4 nanosheets and graphene layers, and the thermal conductivity is 30-60 W m -1 K -1 ; The soluble g-C3N4 nanosheets are two-dimensional g-C3N4 nanosheets prepared by hydrothermal treatment; The mass ratio of the soluble g-C3N4 nanosheets to graphene is 0.1 to 5:1; The preparation method of the graphite phase carbon nitride and graphene composite electric heating film is as follows: (1) Preparation of g-C3N4; Add nitrogen-rich organic matter into a quartz crucible, then place the crucible into a high-energy microwave oven resonant cavity for irradiation treatment to obtain light yellow g-C3N4 powder; (2) Preparation of soluble g-C3N4; The powder is uniformly dispersed in deionized water to obtain a mixed solution, and then ultrasonically treated for 0.5 to 2 hours; after the hydrothermal treatment, the mixture is cooled to room temperature, washed with deionized water and freeze-dried overnight to obtain soluble g-C3N4 nanosheets; (3) Preparation of GO dispersion; First, GO was prepared by the Hummers method: graphite, sodium nitrate, and potassium permanganate were weighed in a ratio of 1:1:3 under ice bath conditions, and then concentrated sulfuric acid was slowly added dropwise into a three-necked flask containing graphite and stirred. The sample was then mixed with sodium nitrate, and the weighed potassium permanganate was added to the three-necked flask in batches, and continued to be stirred, and reacted in a water bath; after adding deionized water to dilute the solution, hydrogen peroxide was gradually added to the three-necked flask, and stirred while adding dropwise until the liquid changed color and separated into layers, and the lower layer of golden viscous liquid was filtered and washed with dilute hydrochloric acid solution and deionized water until neutral, thereby obtaining a graphene oxide solution; (4) Preparation of g-C3N4 / GO composite membrane The soluble g-C3N4 nanosheets are dispersed in the GO solution to obtain a mixture, and then the mixture is placed in an ultrasonic instrument for ultrasonic homogenization, and the g-C3N4 / GO mixed dispersion is vacuum filtered using an organic filter membrane with a pore size of 0.22 μm and a vacuum filtration device, and the composite film is placed in a vacuum drying oven and continuously dried at a temperature of 60° C. for 12 hours to obtain a first composite film; (5) Preparation of g-C3N4 / rGO composite electric heating film; The first composite film is placed in a high-energy microwave oven resonant cavity, the microwave power is adjusted to 3-5W, and the film is kept warm for 3-10s under microwave radiation heating to obtain a g-C3N4 / rGO composite electric heating film.

2. The method for preparing a graphite phase carbon nitride and graphene composite electric heating film according to claim 1, characterized in that: In step (1), the nitrogen-rich organic matter is any one of urea, dicyandiamide, and melamine, or a combination of at least two of them.

3. The method for preparing a graphite phase carbon nitride and graphene composite electric heating film according to claim 1, characterized in that: In step (1), the heating power of the high-energy microwave is 3 to 5 kW.

4. The method for preparing a graphite phase carbon nitride and graphene composite electric heating film according to claim 1, characterized in that: In step (1), the heating reaction time of the high-energy microwave is 1 to 10 minutes.

5. The method for preparing a graphite phase carbon nitride and graphene composite electric heating film according to claim 1, characterized in that: In step (2), the hydrothermal reaction temperature is 150-200°C.

6. The method for preparing a graphite phase carbon nitride and graphene composite electric heating film according to claim 1, characterized in that: In step (2), the hydrothermal reaction is kept warm for 5 to 24 hours.

7. The method for preparing a graphite phase carbon nitride and graphene composite electric heating film according to claim 1, characterized in that: In step (4), the conditions for ultrasonic dispersion are: ultrasonic machine operating frequency 80kHz, power 100W, and room temperature ultrasound for 1-2h.

8. The method for preparing a graphite phase carbon nitride and graphene composite electric heating film according to claim 1, characterized in that: In step (5), in the g-C3N4 / rGO composite membrane, the mass ratio of soluble g-C3N4 to rGO is 0.2-3:

1.

9. A composite electric heating film prepared by the method for preparing a composite electric heating film of graphite phase carbon nitride and graphene as claimed in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method for realizing N-doped grapheme by high-energy microwave vacuum irradiation

    CN103058177A

  • Preparation and application method of carbon nitride-based composite nanometer material

    CN107159288A

  • Preparation method of carbon nitride / graphene composite material with three-dimensional structure

    CN107185576A

  • Visible light responsive type nano-sheet composite photocatalytic film and method for producing the same

    JP2023117409A